2012
DOI: 10.1016/j.brat.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity differences in child and parental outcomes following involvement the PACE program

Abstract: This study investigated ethnic differences in the extent to which engagement (i.e., attendance and quality of participation) in the PACE (Parenting our Children to Excellence) program predicted positive child and parent outcomes. PACE is an 8-week preventive intervention aimed at parents of preschool children. The study investigated the relation of engagement to outcomes in an ethnically diverse sample of 298 African American and 280 European American parents. Overall results demonstrated that engagement in PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Thus, the current state of the literature does not allow determination of whether adapted parent training improves engagement among minority families. However, it is important to note that some of the culturally adapted interventions described relatively high enrollment and/or attendance compared with studies of non-adapted parent training with diverse samples that have reported rates of 45% to 60% enrollment (August, Lee, Bloomquist, Realmuto, & Hektner, 2003;Begle et al, 2012;Brotman et al, 2005) and 45% to 55% average attendance (Begle et al, 2012;Linares, Montalto, Li, & Oza, 2006). Such findings point to the need for studies that compare culturally adapted interventions with non-adapted interventions to determine whether culturally adapted interventions are beneficial for increasing engagement among minority parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the current state of the literature does not allow determination of whether adapted parent training improves engagement among minority families. However, it is important to note that some of the culturally adapted interventions described relatively high enrollment and/or attendance compared with studies of non-adapted parent training with diverse samples that have reported rates of 45% to 60% enrollment (August, Lee, Bloomquist, Realmuto, & Hektner, 2003;Begle et al, 2012;Brotman et al, 2005) and 45% to 55% average attendance (Begle et al, 2012;Linares, Montalto, Li, & Oza, 2006). Such findings point to the need for studies that compare culturally adapted interventions with non-adapted interventions to determine whether culturally adapted interventions are beneficial for increasing engagement among minority parents.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in outcomes associated with disruptive behavior include higher rates of parental stress, school failure, and juvenile justice involvement among minority children with disruptive behavior (Ezpeleta, Keeler, Erkanli, Costello, & Angold, 2001; Fite, Wynn, & Pardini, 2009; Hinojosa et al, 2012). Literature reviews indicating (a) positive outcomes among minority children with disruptive behavior whose parents demonstrate high-intervention attendance (Huey & Polo, 2008; Miranda et al, 2005) and studies demonstrating (b) better outcomes among minority children of parents who are retained in parent training (Begle, Lopez, Cappa, Dumas, & de Arellano, 2012) underscore the importance of identifying potential strategies to maximize enrollment, attendance, and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Enrollment rates in previous studies have ranged from 45% to 60% (August, Lee, Bloomquist, Realmuto, & Hektner, 2003; Begle, Lopez, Cappa, Dumas, & de Arellano, 2012; Brotman et al, 2005), and average attendance has ranged from 45% to 55% of sessions (Begle et al, 2012; Linares, Montalto, Li, & Oza, 2006). Results from the current study are in line with this previous research.…”
Section: Discussionmentioning
confidence: 99%
“…También, los PGEP fueron implementados y evaluados con progenitores de distinta procedencia. Así pues, tres estudios evaluaron intervenciones con progenitores afroamericanos (Begle et al, 2012;Breitenstein et al, 2012;Coard et al, 2007), dos con latinos (Breitenstein et al, 2012;Dumas et al, 2011), uno con euroamericanos (Begle et al, 2012) y otro con inmigrantes chinos (Leung et al, 2011).…”
Section: Características De Los Estudios Seleccionadosunclassified